Beam-to-beam eccentric end plate connections - Experimental comparison to fin plate and partial-depth end plate connections. (June 2019) - Hawxwell, Daniel Allan; Tsavdaridis, Konstantinos Daniel
Abstract: This paper presents a study of eccentric end plate (EEP) beam-to-beam connections as a non-standard detailed design presented in SCI P358 and commonly used for complex geometries where standard simple connections are not suitable. The rotational capacity of EEP connections is often questioned since it should theoretically be a nominally-pinned connection. In this study the rotational behaviour is investigated with a series of moment-rotation experiments and then compared with another two simple connections; a fin plate (FP) connection, and a partial-depth end plate (PDEP_ connection). It is concluded that the EEP connection is semi-rigid with a higher stiffness and strength than the FP and PDEP connections which are found to behave as nominally-pinned. The EEP connection imposed higher forces and thus more deformation was obtained on the supporting member in comparison with the FP or PDEP connections. The concluding recommendation is to only use EEP connections if the specific connection design has been verified to be nominally-pinned or by including the fixity in the frame analysis.